The mediating role of self-criticism, experiential avoidance and negative urgency on the relationship between ED-related symptoms and difficulties in emotion regulation - Rodrigues, Tânia Catarina Fonseca (2022)
Objective: Difficulties in emotion regulation are thought to play a transdiagnostic role across eating disorders (ED). In the current study, we explored with a path analysis the mediating role of self-criticism, experiential avoidance and negative urgency on the relationship between ED-related symptoms and dimensions of difficulties in emotion regulation. Method: Participants were 103 female outpatients recruited at a Portuguese ED hospital unit, diagnosed with an ED, aged 14–60 years old (M = 28.0, SD = 10.5), body mass index (BMI) ranging from 11.72 to 39.44 (M = 20.1, SD = 5.4). Results: The path analysis resulted in a model with an adequate fit to the data (SRMR = 0.05; RMSEA = 0.07 [0.00, 0.12], PCLOSE = 0.269; TLI = 0.97; IFI = 0.99; GFI = 0.95). A final model in which the relationship between ED-related symptoms and dimensions of difficulties in emotion regulation was mediated by self-criticism, experiential avoidance and negative urgency, accounted for a variance of 71% for strategies, 57% for non-acceptance, 62% for impulses, 56% for goals and 20% for clarity. Conclusion: Results suggest that self-criticism, experiential avoidance and negative urgency, combined, are relevant in the relationship between ED-related symptoms and difficulties in emotion regulation. ED treatment and emotion regulation skills may be enhanced through the inclusion of specific components that target self-criticism, experiential avoidance and negative urgency, as they become prominent during the therapeutic process.